Surgical correction of scoliosis in Rett syndrome: cord monitoring and complications - Hammett, T. (Springer Berlin Heidelberg, 2014)
AIM: Rett syndrome is a progressive neurodevelopmental disorder that predominantly affects females and is associated with a high incidence of scoliosis and epilepsy. There is scant published work about intraoperative spinal cord monitoring in these patients and little more regarding the rate of perioperative complications. We investigated our institutions’ experience with both. METHODS: We retrospectively reviewed the records of 11 patients with Rett syndrome who underwent surgical correction of scoliosis at our institution between 2004 and 2010. RESULTS: Eleven patients underwent successful correction of their scoliosis at an average age of 12. Eight of the patients suffered one or more significant complications. The average curve was corrected from 71° to 27°. Successful spinal cord monitoring was achieved in eight of the nine patients where it was attempted. No patient suffered any neurological complications. Average inpatient stay was 18.2 days. CONCLUSION: Scoliosis surgery in patients with Rett syndrome carries a very high rate of complications and an average hospital stay approaching 3 weeks. Both caregivers and surgeons should be aware of this when planning any intervention. These patients frequently have useful lower limb function and spinal cord monitoring is a valid tool to aid in its preservation. We would suggest aggressive optimisation of these patients prior to surgery, with an emphasis on nutrition.